The Effect of Giving A Mixture of Indigofera (Indigofera tinctoria) Flour In Commercial Feedon The Growth of Quail (Coturnix-coturnix japonica) - Jihadul Ullia; Mustaqim; Suryani (Warmadewa University Press, 2024)
This research was carried out at Pak Rusdi's farm, Cot Jabet Village, Gandapura District, Bireuen Regency for 45 days starting in May - July 2023. This research aims to see the effect of a mixture of indigofera flour in commercial feed on the growth of quail. The design used in this research was a Completely Randomized Design (CRD) with 4 treatments and 3 replications. The results of the research can be concluded that the effect of giving a mixture of indigofera flour in commercial feed showed no significant difference (P<0.05) on body weight gain and feed conversion of quail. The highest average body weight gain was seen in treatment P2, namely 2.27 g/head/day and the lowest average was in treatment P3, namely 2.18 g/head/day and the highest average feed conversion was found in treatment P3, namely 10.58 gr/head. /day and the lowest average was in treatment P2, namely 10.18 g/head/day.